Entrepreneurship and the internationalisation of Asian firms : an institutional perspective - Yeung, Henry Wai-Chung. (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2002)
This book provides diverse perspectives on developing-country TNCs from different disciplines, including business history, development studies, geography, political science, and regional studies.
Includes bibliographical references (p. 277-304) and index.
gau 26/05/14
Loans
Keywords: International business enterprises -- Asia; Investments, Asian; Corporations, Asian; Entrepreneurship -- Asia